2020
DOI: 10.1002/anie.202005629
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Active Hybrid Polyoxometalate‐Stabilised Gold Nanoparticles

Abstract: We report the design and preparation of multifunctional hybrid nanomaterials through the stabilization of gold nanoparticles with thiol‐functionalised hybrid organic–inorganic polyoxometalates (POMs). The covalent attachment of the hybrid POM forms new nanocomposites that are stable at temperatures and pH values which destroy analogous electrostatically functionalised nanocomposites. Photoelectrochemical analysis revealed the unique photochemical and redox properties of these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…The POM mediated surface photoactivity was also observed by the photoreduction of silver ions which led to spatially controlled nucleation of small silver nanoparticles exclusively at the surface of POM-Polystyrene conjugate. 150 The use of POMs as protecting ligands for electrostatically stabilised metal(0) nanoparticles and nanocomposites has been nicely reviewed by Weinstock et al 159 Few examples of covalently bound POMs to gold (AuNPs) [160][161][162] and platinum 163 nanoparticles have also been reported using on-purpose designed hybrid POMs. Towards this end, hybrid POMs featuring thiol-terminated alkyl chains have been prepared as capping agents in order to create a strong interaction with the nanoparticles through a thiolate-type binding mode.…”
Section: Mixed-addenda Wells-dawsonmentioning
confidence: 99%
See 1 more Smart Citation
“…The POM mediated surface photoactivity was also observed by the photoreduction of silver ions which led to spatially controlled nucleation of small silver nanoparticles exclusively at the surface of POM-Polystyrene conjugate. 150 The use of POMs as protecting ligands for electrostatically stabilised metal(0) nanoparticles and nanocomposites has been nicely reviewed by Weinstock et al 159 Few examples of covalently bound POMs to gold (AuNPs) [160][161][162] and platinum 163 nanoparticles have also been reported using on-purpose designed hybrid POMs. Towards this end, hybrid POMs featuring thiol-terminated alkyl chains have been prepared as capping agents in order to create a strong interaction with the nanoparticles through a thiolate-type binding mode.…”
Section: Mixed-addenda Wells-dawsonmentioning
confidence: 99%
“…18), and reported that the nanocomposites that were obtained following this strategy exhibited much higher stability to temperature and pH values compared to their electrostatically stabilised analogues. 162 Nanomaterials that combine optical properties of gold nanoparticles with the electro-and photochemical features of the POM framework are of particular interest to obtain multifunctional nanomaterial with potential applications in catalytic and sensing technologies. Polarz et al reported the preparation of the Keggin derivatives [SiW 11 O 39 {Si(CH 2 ) n -SH} 2 O] 4À which were also attached to the surface of gold nanoparticles using thiolatetype binding mode.…”
Section: Mixed-addenda Wells-dawsonmentioning
confidence: 99%
“…Heteropoly acids (HPAs) are unique redox active materials, which have the ability to reversibly accept or donate electrons without structural changes. [25][26][27][28] Such electron sponge behaviour of HPAs has been extensively exploited to use them as electrode active materials for pseudocapacitance. [28][29][30][31][32] Recently, we have successfully developed a kind of underwater adhesive based on HPAs and amino acids (AAs).…”
Section: Introductionmentioning
confidence: 99%
“…This vast family of compounds is reputed for their rich redox properties (Gumerova and Rompel, 2018 ) and photoactivity (Cameron et al, 2018 ) in conjunction with high thermal and oxidative stability (Varga et al, 1998 ; Lv et al, 2012 ). As such, POMs have demonstrated applicability in a wide number of research areas including redox and photoredox catalysis (Wang and Yang, 2015 ), optoelectronics (Chen et al, 2019 ), soft materials (Kastner et al, 2017 ), molecular magnetism (Baldoví et al, 2017 ), photochromic devices (Liu et al, 2006 ), hybrid nanomaterials (Jordan et al, 2019 ; Martin et al, 2020 ), and battery technologies (Huang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%